2015
DOI: 10.1093/heapro/dav062
|View full text |Cite
|
Sign up to set email alerts
|

How Health in All Policies are developed and implemented in a developing country? A case study of a HiAP initiative in Iran

Abstract: Population health is influenced by many factors beyond the control of health system which should be addressed by other sectors through inter-sectoral collaboration (ISC). Countries have adopted diverse initiatives to operationalize ISC for health such as establishment of Councils of Health and Food Security (CHFSs) and development of provincial Health Master Plans (HMPs) in Iran. The literature, however, provides meager information on how these initiatives have been moved into the top policy agenda, how and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In this study, we have also found the MSF useful to examine causal factors across these aspects of the policy process. Other examples of the MSF being used in LMICs or regions include its use in examining policy initiatives in Iran 27 , 37 ; the failure of a health insurance system in Lebanon 38 ; the introduction of a national health insurance scheme in Ghana 26 ; and the development of maternal health policy in India. 28 These studies can serve to broaden our understanding of the policy process – and the utility of MSF as an analytical tool – by drawing out the complexity in different settings and contexts and their influence on policy-making.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have also found the MSF useful to examine causal factors across these aspects of the policy process. Other examples of the MSF being used in LMICs or regions include its use in examining policy initiatives in Iran 27 , 37 ; the failure of a health insurance system in Lebanon 38 ; the introduction of a national health insurance scheme in Ghana 26 ; and the development of maternal health policy in India. 28 These studies can serve to broaden our understanding of the policy process – and the utility of MSF as an analytical tool – by drawing out the complexity in different settings and contexts and their influence on policy-making.…”
Section: Discussionmentioning
confidence: 99%
“…The Kingdon multiple stream model that was originally developed to explore the agenda setting in the United States, has also been applied in several studies in LMICs for policy making and policy analysis including Iran . This model highlights the role of interest groups, advocacy groups and policy entrepreneurs within or outside the governments as agents for coupling the three streams.…”
Section: Discussionmentioning
confidence: 99%
“…Slums de ned as "a densely populated usually urban area marked by crowding, dirty run-down housing, poverty, and social disorganization." (17) and the World Health Organization (WHO) de ned human health as "a state of complete physical, mental, and social well-being and not merely the absence of disease or in rmity." (18).…”
Section: Terms' De Nitionmentioning
confidence: 99%
“…As, slum-speci c health priorities might be different from the national or even urban area (17), this review aimed to provide an inclusive picture of slum's health related situations in Iran based on conducted studies for implementing multiple interventions for multiple outcomes.…”
Section: Introductionmentioning
confidence: 99%